PENANAMAN NILAI-NILAI KARAKTER ISLAMI MELALUI KEGIATAN RUTIN DI SMP ISLAM SABILAL MUHTADIN BANJARMASIN - Ahmad Mahfuz (Al-Falah: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2019)
This study discusses the planting of Islamic character values through routine activities in Sabilal Muhtadin Islamic Junior high school Banjarmasin. The purpose of this research is to further the planting of Islamic character values through routine activities in junior high school Sabilal Muhtadin Banjarmasin and the factors that influence it. The subject in this study is deputy principal of curriculum, teacher of PAI, the deputy 9 A, B, and C. Whereas, the object in this research is a routine activity that imparts the values of Islamic characters in the Islamic SMP Sabilal Muhtadin Banjarmasin and factor's that affect it. In the collection of authors data using interview techniques, observations, and documentation. While the data processing technique is done by editing, data classification, and data interpretation, it is subsequently analyzed in a qualitative descriptive. Based on the results of the research, it is known that the planting of Islamic character values through routine activities at SMP Islam Sabilal Muhtadin Banjarmasin was good. It is seen with the Islamic character shown by the most mature students or from the 9th grade which shows 18 Islamic characters who are the basis of character education in the Islamic SMP Sabilal Muhtadin Banjarmasin. The planting of Islamic characters is not separated from the builds factors, the supporting factor is the teacher who always builds in the cultivation of Islamic character and infrastructure, and the environment that supports the planting of Islamic characters So it went well. Keywords: value planting, Islamic character, routine activities